(untitled) - Dillon, Matthew (London, 1994)
This book presents a wide range of documents on Greck social and political history from 800 BC to 399 BC, from over the Greck world. Evidence fprr development within Greece during this period is taken not only from historical sources, but from inscriptions, graffti. law codes, epitaphs, decrees, drama and poetry. The book is arranged thematically, and includes sections devoted to Sparta, tyranny, the position of women, slavery, colonization, the city-state and religion
Keywords: Greece,Greece,Greece; Antiquities,Civilization,Politics and government